PENGARUH KEMUDAHAN PENGGUNAAN DAN KEPERCAYAAN KONSUMEN TERHADAP NIAT BELI DENGAN MEDIA SOSIAL SEBAGAI VARIABEL ANTESEDEN KEMUDAHAN PENGGUNAAN PADA APLIKASI TRAVELOKA - Elsa Saputri Widya Ningrum; Janfry Sihite (Journal of Fundamental Management (JFM), 2023)
When the competition is fierce, which causes purchase intention to be very important for a company. Purchase intention is also a factor that determines a company in marketing a product so that the product offered raises the intention to buy consumers. in the era of many people who want to travel, as evidenced by shopback data in 2019 showing that the current occurrence of online travel ticket bookings in 2018 is 260 percent, this spike continues to increase every year. The purpose of this thesis is to determine the Effect of Ease of Use and Consumer Trust on Purchase Intentions with Social Media as Antecedent Variables of Ease of Use in the Traveloka Application. The sample used in this study was 150 respondents. The sampling method was carried out by the purposive sampling method. This study uses SEM data analysis techniques and data processing using Partial Least Square (PLS). The results of this study indicate that social media has a positive effect on ease of use, ease of use has a positive effect on purchase intention and consumer trust has a positive effect on purchase intention.